A model development of community-based and digital tourism village in Belakang Padang - Rais, Syafruddin; Faridah, Anni; Yuliana, Yuliana; Ambiyar, Ambiyar (International journal of health sciences, 2022)
This study aims to develop a community-based and digital tourism village model, then this model will be evaluated for its validity and applicability. The 4-D research methodology is employed as the research method. The subjects of this research are experts, tourism managers, and the community. The six schemes that are implemented yield the following results: 1. Tourist village; 2. Building community-based and digital tourism villages and business plans; 3. Establishing tour packages, which include tour packages for tourist destinations, 4); Community; 5); The official website for the digital tourism village; and 6); The vision and mission of the Belakang Padang District. The outcomes of the product category validation are reliable, applicable, and practical. It can be concluded that this model is feasible to be implemented to develop tourist villages.